Nervous system medications and suicidal ideation and behaviour:the Northern Finland Birth Cohort 1966 - Rissanen, I. (Ina) (Oulun yliopisto, 2015)
Abstract The aim of this thesis was to explore the associations between the use of nervous system medications and suicidal ideation and behaviour in various different diagnostic groups in a large population-based cohort. Information on prescribed antipsychotic, antidepressant, benzodiazepine and antiepileptic medications within the Northern Finland Birth Cohort 1966 was collected from the register of the Social Insurance Institution of Finland and from a postal questionnaire sent to all cohort members in 1997. The presence of suicidal ideation and depression and anxiety symptoms was assessed via the Hopkins Symptom Checklist-25 questionnaire in 1997. Data on suicides were collected from the cause-of-death statistics and on suicide attempts from the Finnish Care Register for Health Care in a 15-year follow up. The use of antipsychotic, antidepressant, or benzodiazepine medication was associated with increased suicidal ideation, suicide attempts, and suicides. Antiepileptic medication was not associated with increased suicidality. The polypharmacy of nervous system medications was associated with increased suicidality. All nervous system medications were associated with increased severity of depression and anxiety symptoms. When depression and anxiety symptoms were taken into account, most of the associations between medication and suicidal ideation were statistically non-significant. Regarding specific groups, among those who did not have psychosis, high doses of antipsychotic medication correlated particularly with increased suicidal ideation even when other symptoms of depression and anxiety were taken into account. Among those with insomnia, the use of antidepressant medication associated with increased suicidal ideation also when other symptoms were taken into account. Although nervous system medication is associated with increased suicidal ideation, the association with other symptoms is also strong, and therefore it could not be stated that medication associates specifically with suicidal ideation. However, ...